PENGEMBANGAN ALAT PENDETEKSI ASAP PADA KAMAR HOTEL BERBASIS INTERNET OF THINGS (IOT) DI INDRAMAYU - Margana, Ferry Kurniawan; Pauzan, Muh (Universitas Semarang, 2024)
The development of IoT-based smoke detectors using NodeMcu ESP8266 and smoke sensors has achieved satisfactory results. This tool has succeeded in providing an effective solution as a responsive early detection of fire. The implementation of remote monitoring through the website allows access to smoke detection information from far-flung locations, providing flexibility and affordability in security surveillance. NodeMcu ESP8266 as an IoT platform proved to be the right choice, bringing the ease of connectivity of tools with the internet. The device's quick response to the presence of smoke at various sensor distances confirms its reliability in detecting potential fires. The success of this research highlights the great potential of IoT technology in improving the level of security, especially in detecting fire threats efficiently. With tested and responsive tools, further implementation and development of functionality can be explored. Overall, the development of smoke detectors promises to make a positive contribution to the understanding and application of IoT technology in the context of public security and safety. Keywords: IoT-Based Smoke Detectors, NodeMcu ESP8266, Remote Monitoring, Fire Early Warning Systems, Sensor Technology. ABSTRAKPengembangan alat pendeteksi asap berbasis IoT menggunakan NodeMcu ESP8266 dan sensor asap telah mencapai hasil yang memuaskan. Alat ini berhasil memberikan solusi efektif sebagai pendeteksi dini kebakaran yang responsif. Implementasi monitoring jarak jauh melalui website memungkinkan akses informasi deteksi asap dari lokasi yang berjauhan, memberikan fleksibilitas dan keterjangkauan dalam pengawasan keamanan. NodeMcu ESP8266 sebagai platform IoT terbukti menjadi pilihan yang tepat, menghadirkan kemudahan konektivitas alat dengan internet. Respons cepat alat terhadap keberadaan asap pada berbagai jarak sensor menegaskan kehandalannya dalam mendeteksi potensi kebakaran. Kesuksesan penelitian ini menyoroti potensi besar teknologi IoT dalam meningkatkan tingkat keamanan, khususnya dalam mendeteksi ancaman kebakaran secara efisien. Dengan alat yang teruji dan responsif, implementasi lebih lanjut dan pengembangan fungsionalitas dapat diexplorasi. Secara keseluruhan, pengembangan alat pendeteksi asap ini menjanjikan kontribusi positif terhadap pemahaman dan penerapan teknologi IoT dalam konteks keamanan dan keselamatan masyarakat.